Validation of CFD Simulation for Wind Velocity Measurement in High-Rise Apartment Buildings in Surabaya - Fristatesa Andriani; Arsi Dinapradipta; Fransciscus Teddy Badai Samodra (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2019)
The double-loaded circulation system makes the performance of cross ventilation in apartment buildings to be ineffective. Therefore, the alternative of the ventilation system is necessary to be examined in order to obtain an adequate velocity comfort. To determine the appropriate alternatives, we need to discover the suitable software. In this study, a validation of a simulation method using Computational Fluid Dynamics (CFD) is carried out to determine whether the software is capable to provide useful analysis for high-rise apartments. Based on the results, the validation of the correlation value (R²) between the measurement and simulation is 0.67. It shows that the influence between variables is sufficient.